Growth patterns of activity of daily living disability and associated factors among the Chinese elderly: A twelve-year longitudinal study. (March 2022) - Huang, Xitong; Zhang, Minqiang; Fang, Junyan
Highlights: The majority of the oldest old in China did not exhibit any ADL disability. Two development trajectories of ADL disability among the elderly were identified: the Slightly Increasing Group and Quickly Increasing Group. Doing housework could help maintain ADL capabilities. Stroke or dementia may accelerate the deterioration of ADL ability. Abstract: Objectives: The acceleration of population aging has brought a lot of attention to the disability among older populations, but existing results about the development patterns of disability were mixed. The current study aimed to identify the potential different development patterns of disability and the influential factors using a large, nationally representative sample of the Chinese elderly. Methods: : We adopted a five-wave longitudinal dataset from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), and 1, 654 elderly aged 65 and over were obtained. Disability was measured by the Katz index scale grading individuals on a scale of difficulty to carry out activities of daily living (ADL). We utilized the conditional growth mixture model (GMM) to identify various development patterns and associated factors. Results: : Compared with those without disability ( n  = 1, 140), individuals with ADL disability ( n  = 514) were more likely to be old, female, or Han ethnic, eat more healthy food and suffer from chronic disease. Two groups with distinct trajectories of ADL disability were identified, including the Slightly Increasing Group and the Quickly Increasing Group. People who did less housework (OR=0.33, 95%CI: 0.12−0.90; p  = 0.030), suffered from stroke (OR=5.39, 95%CI: 1.43−20.35; p  = 0.013) or dementia (OR=10.29, 95%CI: 1.01−104.44; p  = 0.049) were more likely to be classified into the Quickly Increasing Group. Conclusion: : There existed two development patterns of ADL disability among the Chinese elderly. Besides, doing housework could help prevent the deterioration of disability, and suffering from stroke or dementia may accelerate the deterioration of ADL ability in later years. Implications are provided for public health interventions.